1992
DOI: 10.1002/bjs.1800790125
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the healing of distal amputations performed for lower limb ischaemia

Abstract: A total of 235 toes were amputated during 125 operations on 100 consecutive patients with lower limb ischaemia. The overall amputation wound healing rate for the series was 58.4 per cent and limb salvage was achieved in 66 patients. Toe amputation was performed under local anaesthesia in 57 cases and 32 (56 per cent) of these healed primarily, not significantly different from the healing rate of 41 (60 per cent) of 68 under general anaesthesia. Reconstructive arterial surgery was performed in conjunction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Other studies have shown similar wound healing rates between diabetics and non-diabetics. [5][6][7]14 In our study, diabetes was not predictive of poor outcomes, though the study cohort consisted of few non-diabetic patients and lacked data on HbA1c glucose control.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Other studies have shown similar wound healing rates between diabetics and non-diabetics. [5][6][7]14 In our study, diabetes was not predictive of poor outcomes, though the study cohort consisted of few non-diabetic patients and lacked data on HbA1c glucose control.…”
Section: Discussionmentioning
confidence: 84%
“…Diabetic and non-diabetic populations were included since they have been reported to have similar healing rates after minor amputations. [5][6][7] Secondary objectives included examining clinical and haemodynamic factors that predict healing and conversion to major amputation.…”
Section: Introductionmentioning
confidence: 99%
“…[60,61] Once hallux has gone under amputation, changes in mechanical force and pressure on the foot may increase the likelihood of developing further lesions, most probably within 6 months. [62] Studies by Byrne et al 1992 andYeager et al 1998 showed that revascularization may not prevent reamputation as patients undergoing revascularization procedures are likely to have severe ischaemic disease. [63,64]…”
Section: Foot Amputationmentioning
confidence: 99%
“…[62] Studies by Byrne et al 1992 andYeager et al 1998 showed that revascularization may not prevent reamputation as patients undergoing revascularization procedures are likely to have severe ischaemic disease. [63,64]…”
Section: Foot Amputationmentioning
confidence: 99%
“…Dillingham et al (10) estimated that .37% of patients with diabetes who had a toe amputation in 1996 had a second LEA within 12 months, proportions that exceeded reamputation rates following a transtibial (25%) or a transfemoral (18%) amputation. Although there are more than a dozen studies that have assessed risks of subsequent amputations among patients who underwent toe or ray (a more extensive toe amputation that involves excision of the metatarsal head) amputation(s) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), most prior studies were small; only four studies included .200 patients (10,15,20,22), and of these, the one by Dillingham et al (10) was the largest with 889 U.S. Medicare beneficiaries. One important limitation of this study was the inability to distinguish subsequent amputations on the ipsilateral limb from amputations on the contralateral limb because information on laterality was not available.…”
mentioning
confidence: 99%